2013
DOI: 10.1039/c2sm27016a
|View full text |Cite
|
Sign up to set email alerts
|

Design principles for superamphiphobic surfaces

Abstract: To predict the properties of superamphiphobic layers we analyzed the wetting of a square and a hexagonal array of vertical pillars composed of spheres (radius R) partially sintered together. Apparent contact angles above 150 are obtained by pinning of a non-polar liquid surface at the underside of the top sphere resulting in a Fakir or Cassie state. Analytical equations are derived for the impalement pressure in the limiting case A 0 [ R 2 , where A 0 is the area of the regular unit cell containing a single pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
205
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 201 publications
(219 citation statements)
references
References 80 publications
9
205
0
1
Order By: Relevance
“…Interestingly,  Adv ,  Rec , and  SA for hexadecane on the beadsonly surface are 156°, 150° and 5°, respectively. In comparison, the beads-on-strings and fibers-only surfaces shows a slightly 10 higher CAH with  Adv / Rec values of 153°/141° and 153°/134°, respectively. Recently, the same research group demonstrated that similar textured surfaces can also be fabricated by spraying the FD-POSS/PMMA blend.…”
Section: Spraying a Copper Perfluorooctanoate Suspensionmentioning
confidence: 91%
See 4 more Smart Citations
“…Interestingly,  Adv ,  Rec , and  SA for hexadecane on the beadsonly surface are 156°, 150° and 5°, respectively. In comparison, the beads-on-strings and fibers-only surfaces shows a slightly 10 higher CAH with  Adv / Rec values of 153°/141° and 153°/134°, respectively. Recently, the same research group demonstrated that similar textured surfaces can also be fabricated by spraying the FD-POSS/PMMA blend.…”
Section: Spraying a Copper Perfluorooctanoate Suspensionmentioning
confidence: 91%
“…The surface can be roughly deemed as superantiwetting if both water and 'oils' can move freely on the surface without any sticking. However, to characterize a superantiwetting surface quantitatively, precise determinations of static 10  CA and CAH, which are normally performed with commercial instruments, are needed. More than 200 years ago, Thomas Young, the genius polymath who made major contributions to vision, physiology, sound, light, 20 language, solid mechanics, and Egyptology, described the forces acting on a liquid droplet spreading on a surface (Fig.…”
Section: Characterization Of Superamphiphobicitymentioning
confidence: 99%
See 3 more Smart Citations